2008
DOI: 10.1074/jbc.m707632200
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Transitions in Adenylate Kinase

Abstract: Large conformational changes in the LID and NMP domains of adenylate kinase (AKE) are known to be key to ligand binding and catalysis, yet the order of binding events and domain motion is not well understood. Combining the multiple available structures for AKE with the energy landscape theory for protein folding, a theoretical model was developed for allostery, order of binding events, and efficient catalysis. Coarse-grained models and nonlinear normal mode analysis were used to infer that intrinsic structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
115
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 39 publications
13
115
0
1
Order By: Relevance
“…2b, the ATP and AMP domain movements are correlated, disfavouring conformations where the LID is open and the AMPbd is closed. Our findings agree with free energy calculations[34], molecular dynamics simulations[35] as well as with normal mode analysis [33], [36]. Although it is impossible to derive the closure pathway from equilibrium data, the conformational states observed favour a step-wise mechanism in which LID closure takes place before AMPbd closure.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…2b, the ATP and AMP domain movements are correlated, disfavouring conformations where the LID is open and the AMPbd is closed. Our findings agree with free energy calculations[34], molecular dynamics simulations[35] as well as with normal mode analysis [33], [36]. Although it is impossible to derive the closure pathway from equilibrium data, the conformational states observed favour a step-wise mechanism in which LID closure takes place before AMPbd closure.…”
Section: Resultssupporting
confidence: 89%
“…5% at 37°C;[32] under the conditions used in this study (25°C) this state has a low population (<1%). Similarly, cracking of the AMPbd along the closing mechanism may play a role [26], [33]. However, cracking occurs at the transition state, and therefore has a very low population.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, both conformations A and B must correspond to finite segments of the ξ space, which means that conformations similar to A must have ξ close to ξ( A ) and vice versa, a region of ξ ≈ ξ( A ) must only contain conformations similar to A (the statement has to be true for conformation B as well). In some cases, the topology of the landscape or allosteric motions themselves can provide a good, physically meaningful collective coordinate [21,22]. The new path coordinate that we propose works for general case.…”
Section: Introductionmentioning
confidence: 99%
“…This led us to the hypothesis that functional regions in proteins may add roughness to the landscape because they are under separate evolutionary pressure than areas used for efficient folding. For example, structure-based simulations with adenylate kinase demonstrated that the introduction of frustration induced conformational transitions associated with enzymatic catalyisis through specific unfolding, or cracking (20,21). Folding simulations with Csk and IL-1β successfully captured long range communication to functional sites (22,23).…”
mentioning
confidence: 99%